Pendidikan Perdamaian dalam Mengatasi Bullying di Sekolah - Prasetyo, Zanuar Barep; Poniman, Poniman (Jurnal Ilmiah Psyche, 2025)
Peace education has become a major focus in efforts to prevent violence and build positive character in young people. This study aims to explore the effect of peace education programs on reducing bullying behavior in schools. This study uses a qualitative approach with a case study design, involving in-depth interviews with teachers, students, and education practitioners. Data were collected through semi-structured interviews, observations, and documentation related to the implementation of peace education programs in several schools in Indonesia. The results of the study indicate that peace education programs that focus on developing empathy, social skills, and non-violent communication can significantly reduce bullying incidents, improve relationships between students, and create a more positive school climate. These findings indicate the importance of value education and emotional skills in creating a safe and inclusive learning environment. The contribution of this study lies in providing empirical evidence on the effectiveness of peace education programs in the context of Indonesian education, as well as its implications for education policy and the development of social programs in schools.